EMERGING CASES OF MULTI DRUG RESISTANT TUBERCULOSIS - Denise Utami Putri (Faculty of Medicine Universitas Kristen Duta Wacana, 2016)
Tuberculosis (TB) is one of communicable disease caused by Mycobacterium genus. It is widely spread throughout the world, with at least one third of people is estimated to possess latent TB, a state where infection occurs, but does not develop disease symptoms.1 Indonesia, world’s 4th most populous country, has the highest incidence of TB cases in South East Asia, and 2nd highest globally. It affects more than 1 million people, and has caused more than 100,000 deaths during 2014